Creating a whole institution approach to in-service training in sexual and reproductive health in Uganda. Issue 1 (10th September 2015) - Graffy, Jonathan; Capewell, Sarah J; Goodhart, Clare; Rwamatware, Birungi Mutahunga
Abstract : Background: Uganda has one of the world's highest fertility rates, and high unmet need for family planning, even when clients have contact with health facilities. Misconceptions about contraceptive side effects and inadequate training for healthcare workers contribute to this. Aim: To develop and evaluate in-service training for family planning, across a whole institution. Design: Course evaluation. Impact on services. Methods: Following a needs assessment, two courses were developed, adapting WHO's Training Resource Package for Family Planning. All staff were offered level 1 training (five 1 h sessions). The 30 h level 2 course aimed to train clinical staff to certificate level; assessed by written exam, consultation skills and presentations. Quantitative evaluation assessed changes in pre-course and post-course knowledge and confidence scores. Participant feedback was analysed thematically. Results: Of the hospital's 76 clinical staff, 44 attended some training. Of these, 21 attended and 19 completed level 2. Mean knowledge scores increased from 15.9 (SD 4.5) to 20.8 (SD 3.1)/26 (95% CI 4.9 (2.5–7.2)). Confidence rose from 8.1 (SD 1.5) to 9.5 (SD 0.5) (95% CI 1.4 (0.7–2.2)). Nine were accredited to fit intrauterine devices and implants, and three just implants. Screening for unmet need is being introduced and outreach work aims to overcome barriers to adoption of family planning. Conclusions: Brief in-service training improves health workers' knowledge and skills, corrects misconceptions and increases the priority given to family planning. When aligned to local need and the culture of the institution, training can prompt moves to address unmet need for family planning.